Um novo jeito de se fazer dissertação: letramentos acadêmicos e internacionalização - Nara Nilia Marques Nogueira (2017)
The writing of students has been widely focused in scientific research in the area ofLinguistic Studies, whereas teachers´ literacy practices have not yet deserved the sameemphasis. In this study, we aim at turning the attention to the latter, in order to show thatwhen it comes to academic writing, learning is constantly sought by all. The presentresearch had the purpose of investigating academic literacy practices occurred in aBrazilian higher education institution and the impact of such practices on itsinternationalization process, through the lens of university professors. The research wasconducted in the context of the Workshop Researcher Connect, a workshop designed toassist academic professionals who are required to communicate in English in internationaland multicultural settings. Seventeen people attended the workshop, which took place atUniversidade Federal de Minas Gerais (UFMG). The data collection for this case studyconsisted in applying questionnaires prior to the workshop and doing interviews after it.Some data pointed to recent academic changes, such as the alternative format of thesesand dissertations, and this resulted in the use of such format in this thesis. The discoveriesof this study have been divided in four scientific articles. The first brings reflections andexamples concerning the alternative format, as well as highlights productivityrequirements present in the academic world. The second article shows that neitherteachers, nor students are going to be fully prepared to write and publish in English. Thethird depicts features that are commonly hidden in the internationalization process.Finally, the fourth article demonstrates that collaboration is paramount in the producingand sharing of research. The academic literacy practices, intrinsically social activities, areseen as indispensable to effective and integrative internationalization processes.